Female veteran transition: exploring gendered power relations, discipline and decision making - Micklewright, Caroline; Allen, Robby A. (Wiley, 2026)
This paper investigates how military life affects the decision making of female RAF veterans during transition into the civilian world. By adopting a longitudinal approach and analyzing interviews conducted over 3 years this study explores the relationship between how normalized gendered militarized behaviors and idealized military aspirational identities affect choices made during transition out of the military. Disruptions to this idealized identity brought on by the decision to leave the military trigger recognition of and adjustments to the sense of self. Female veterans' consistency of self is supported through this disruption by drawing on deeply valued aspects of aspirational identity while rejecting others. The study has contributed to theory by demonstrating how gendered discipline and power combine to influence female veterans’ ways of being and support aspects of aspirational identities as they transition into civilian life and face disruptions caused by differences in gendered expectations within military and wider society. By design, this research focused on a limited number of female veterans' experiences as they left the RAF, allowing a hitherto underexplored veteran cohort to be better understood.
Keywords: female veterans; identity; transition; 44 Human Society; Gender Studies; 3505 Human resources and industrial relations; 4410 Sociology